E-179 Tactile deformable soft robots for endovascular microcatheter navigation, placement and stability. (4th August 2020) - Gopesh, T; Wen, J; Santiago-Dieppa, D; Yan, B; Scott-Pannell, J; Khalessi, A; Norbash, A; Friend, J
Abstract : Endovascular procedures are limited by an absence of effective actuation methods for navigation and precise device positioning. The existing panoply of passive guidewires and catheters for the treatment of cerebral aneurysms, in particular, leaves neurointerventionists without a treatment option in at least 25% of patients. A key reason is the inability to steer the tip of the microcatheters in vivo. We overcome this problem with sub-millimeter diameter hydraulically-actuated hyperelastic polymer devices connected over a 160 cm length. These provide controlled 3D orientation of acute tip curvatures beyond 180 degrees at pressures of 400kPa that achieves stable coil deployment in vivo. This method uses saline as the working fluid, and forms a closed system from the steerable tip to the hydraulic actuator offering safety, ease of use, and design flexibility absent in approaches that require external actuation. Disclosures: T. Gopesh: None. J. Wen: None. D. Santiago-Dieppa: None. B. Yan: None. J. Scott-Pannell: None. A. Khalessi: None. A. Norbash: None. J. Friend: None.